Bio-inspired ZnWO4−x exhibiting vacancy-driven UV-to-NIR photodegradation of antibiotics in wastewater. Issue 2 (April 2023) - Osotsi, Maurice I.; Ling, Xin; Fu, Siqi; Xiong, Yuqin; Zhang, Wang; Di, Zhang
Abstract: Complex structures of antibiotics inhibit their breakdown by conventional removal techniques, resulting in persistent environmental pollution and breeding of deadly bacteria, that pose disastrous human health implications. As a remedy, we prepared BW-ZnWO4−x photocatalyst by combining Papilio paris (P. paris) wings as supporting substrates and templating frameworks and oxygen vacant ZnWO4 through modified functionalization and solvothermal processes. The BW-ZnWO4−x photocatalyst exhibited narrowed bandgap, broader photo-absorption, ∼6-fold high surface area and inhibited charge carrier recombination. Consequently, BW-ZnWO4−x photocatalyst degraded 98 %, 94 % and 85 % of levofloxacin (LVFX) antibiotic and 96 %, 93 % and 83 % of tetracycline (TC) antibiotic under ultraviolet (UV), visible and near-infrared (NIR) irradiation, respectively in 60 min. Comparatively, hydrothermally synthesized pristine ZnWO4 photocatalyst (denoted: P-ZnWO4 ) degraded 83 %, 82 %, 59 % of LVFX antibiotic and 85 %, 79 %, 50 % of TC antibiotic under UV, visible and NIR light irradiation, respectively. Moreover, the BW-ZnWO4−x photocatalyst demonstrated real-world applicability by degrading 95 %, 92 % and 78 % of hexavalent chromium (Cr VI) under UV, visible and NIR light irradiation, respectively. Therefore, these results could be insightful in development of bio-inspired materials for solar harvesting and storage systems, security systems and water treatment applications. Graphical Abstract: ga1 Highlights: Oxygen vacant ZnWO4-x samples were synthesized by modified solvothermal method. Functionalized P. paris wings reduces hydrophobicity and generates functional active sites for semiconductor attachment. Aqueous solution attachment of oxygen vacant ZnWO4-x in porous P. paris wing structures, producing BW-ZnWO4-x . BW-ZnWO4-x photocatalyst degraded levofloxacin, tetracycline and hexavalent chromium.